Connecting the multiple dimensions of global soil fungal diversity - Mikryukov, Vladimir; Dulya, Olesya; Zizka, Alexander; Bahram, Mohammad; Hagh-Doust, Niloufar; Anslan, Sten; Prylutskyi, Oleh; Delgado-Baquerizo, Manuel; Maestre, Fernando T; Nilsson, Henrik; Pärn, Jaan; Öpik, Maarja; et al. (Science advances, 2023)
How the multiple facets of soil fungal diversity vary worldwide remains virtually unknown, hindering the management of this essential species-rich group. By sequencing high-resolution DNA markers in over 4000 topsoil samples from natural and human-altered ecosystems across all continents, we illustrate the distributions and drivers of different levels of taxonomic and phylogenetic diversity of fungi and their ecological groups. We show the impact of precipitation and temperature interactions on local fungal species richness (alpha diversity) across different climates. Our findings reveal how temperature drives fungal compositional turnover (beta diversity) and phylogenetic diversity, linking them with regional species richness (gamma diversity). We integrate fungi into the principles of global biodiversity distribution and present detailed maps for biodiversity conservation and modeling of global ecological processes.
Keywords: ekosystém; půda; Phylogeny; lidé; půdní mikrobiologie; Biodiversity; Fungi; Soil Microbiology; Ecosystem; fylogeneze; houby; Humans; Soil; biodiverzita